Knowledge and awareness of the Saudi general public toward epistaxis: a cross-sectional study - Assiri, Abdullah M. (Frontiers in Public Health, 2024)
Background Epistaxis is one of the most common ear, nose, and throat (ENT) emergencies that present to the emergency or primary care centers. Study aim This study aimed to assess the knowledge of the Saudi general public toward epistaxis. Methods This study adopted a cross-sectional analytical study design. The questionnaire link was distributed using social media channels. The participants were adult Saudi nationals that live in Saudi Arabia. The data was collected using a self-administered questionnaire that assessed knowledge related to epistaxis. The knowledge score was calculated using the 10 knowledge evaluation questions. Each correct response was assigned a value of “one.” The scores ranged from “zero” to “ten,” with higher scores signifying greater knowledge. A percentage score was computed, and the participants’ knowledge was classified as poor (% score: ≤50%), moderate (% score: 51 to 70%), and good (% score: 71 to 100%). Statistical Package for Social Sciences (SPSS) version 26 was used for statistical analysis. Results The study included 452 participants of whom 70.1% were females. Married individuals comprised 60.8% of the sample. The prevalence of self-reported epistaxis was 43.6% in the last 6 months. Among the participants, 42.9%, had “Poor” knowledge score, followed by 39.6% who had “moderate” score, and 17.5% had “Good” score. These results show that most participants had poor to moderate knowledge, with a minority demonstrating a good level of knowledge. All demographic variables have significantly influenced the adequacy of knowledge about epistaxis. Furthermore, participants who believed that the general public has insufficient knowledge on epistaxis had a significantly lower knowledge score (p = 0.001). Conclusion The present study found a non-satisfactory, low-to-moderate knowledge level of the Saudi general public toward epistaxis. We propose emphasizing public knowledge and education about first aid for epistaxis because proper first aid can minimize significant complications when done properly.